Urinary Glycosaminoglycans Predict Outcomes in Septic Shock and Acute Respiratory Distress Syndrome - Schmidt, Eric P.; Overdier, Katherine H.; Sun, Xiaojun; Lin, Lei; Liu, Xinyue; Yang, Yimu; Ammons, Lee Anne; Hiller, Terra D.; Suflita, Matt A.; Yu, Yanlei; Chen, Yin; Zhang, Fuming; et al. (American journal of respiratory and critical care medicine, 2016)
Degradation of the endothelial glycocalyx, a glycosaminoglycan (GAG)-rich layer lining the vascular lumen, is associated with the onset of kidney injury in animal models of critical illness. It is unclear if similar pathogenic degradation occurs in critically ill patients. To determine if urinary indices of GAG fragmentation are associated with outcomes in patients with critical illnesses such as septic shock or acute respiratory distress syndrome (ARDS). We prospectively collected urine from 30 patients within 24 hours of admission to the Denver Health Medical Intensive Care Unit (ICU) for septic shock. As a nonseptic ICU control, we collected urine from 25 surgical ICU patients admitted for trauma. As a medical ICU validation cohort, we obtained serially collected urine samples from 70 patients with ARDS. We performed mass spectrometry on urine samples to determine GAG (heparan sulfate, chondroitin sulfate, and hyaluronic acid) concentrations as well as patterns of heparan sulfate/chondroitin sulfate disaccharide sulfation. We compared these indices to measurements obtained using dimethylmethylene blue, an inexpensive, colorimetric urinary assay of sulfated GAGs. In septic shock, indices of GAG fragmentation correlated with both the development of renal dysfunction over the 72 hours after urine collection and with hospital mortality. This association remained after controlling for severity of illness and was similarly observed using the inexpensive dimethylmethylene blue assay. These predictive findings were corroborated using urine samples previously collected at three consecutive time points from patients with ARDS. Early indices of urinary GAG fragmentation predict acute kidney injury and in-hospital mortality in patients with septic shock or ARDS. Clinical trial registered with www.clinicaltrials.gov (NCT01900275).